Health Promotion in an Age of Normative Equity and Rampant Inequality - Ronald Labonté (Kerman University of Medical Sciences, 2016)
The world was different when the Ottawa Charter for Health Promotion was released 30 years ago. Concerns over the environment and what we now call the 'social determinants of health' were prominent in 1986. But the acceleration of ecological crises and economic inequalities since then, in a more complex and multi-polar world, pose dramatically new challenges for those committed to the original vision of the Charter. Can the 2015 Sustainable Development Goals (SDGs), agreed to by all the world's governments, offer a new advocacy and programmatic platform for a renewal of health promotion's founding ethos? Critiqued from both the right and the left for, respectively, their aspirational idealism and lack of political analysis, the SDGs are an imperfect but still compelling normative statement of how much of the world thinks the world should look like. Many of the goals and targets provide signals for what we need to achieve, even if there remains a critical lacuna in articulating how this is to be done. The fundamental flaw in the SDGs is the implicit assumption that the same economic system, and its still-present neoliberal governing rules, that have created or accelerated our present era of rampaging inequality and environmental peril can somehow be harnessed to engineer the reverse. This flaw is not irrevocable, however, if health promoters - practitioners, researchers, advocates - focus their efforts on a few key SDGs that, with some additional critique, form a basic blueprint for a system of national and global regulation of capitalism (or even its transformation) that is desperately needed for social and ecological survival into the 22nd century. Whether or not these efforts succeed is a future unknown; but that the efforts are made is a present urgency.